Inovasi dalam Keuangan Syariah dan Dampaknya terhadap Perdagangan Internasional: Sukuk di Pasar Global - NUR ANNISA, LAILITA (Jurnal Ilmiah Ekonomi Islam, 2024)
This research analyses innovations in Islamic finance and their impact on international trade, with a particular focus on sukuk instruments in the global market. Islamic finance has experienced significant growth in recent decades, and sukuk as one of the main products shows great potential in supporting cross-border economic activity. This research explores how sukuk, as a shariah-compliant financing instrument, has been developed and implemented in various international markets. The research method used includes qualitative analysis of secondary data from various sources, including academic literature and official websites. The results show that innovations in sukuk, such as the development of green sukuk and waqf sukuk, not only increase financial inclusion but also have a positive impact on economic stability and environmental sustainability. Sukuk has proven to be an effective tool in raising funds for large infrastructure projects in emerging and developing countries.This research concludes that innovations in Islamic finance, particularly sukuk, have an important role to play in strengthening international trade and fuelling global economic growth. Policy recommendations are suggested to improve regulations and frameworks that support the further development of sukuk in the global market.